Design & Simulation of MHD Antenna for Wireless Applications (International Journal of Engineering and Computer Science, 2017)
This paper investigate stacked cylindrical DRA,s placed on concentric annular rings . These hybrid nature of structure is operating under controlled electric fields and magnetic fields. Higher gain has been reported in this work when electric bias is given under magnetic bias bandwidth of the antenna is enhanced by making little bit compromise on the Gain. Frequency shift has also been notice during magnetic and electric bias condition .This can be wisely used for getting reconfigureabilty.